2008
DOI: 10.1093/hmg/ddn232
|View full text |Cite
|
Sign up to set email alerts
|

Edar and Troy signalling pathways act redundantly to regulate initiation of hair follicle development

Abstract: The development of ectodermal organs requires signalling by ectodysplasin (Eda), a tumor necrosis factor (TNF) family member, its receptor Edar and downstream activation of the nuclear factor kappaB (NF-kappaB) transcription factor. In humans, mutations in the Eda pathway components cause hypohidrotic ectodermal dysplasia, a syndrome characterized by missing teeth, sparse hair and defects in sweat glands. It has been postulated that Eda acts redundantly with another TNF pathway to regulate ectodermal organogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
61
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 55 publications
8
61
0
Order By: Relevance
“…These data, along with the present work, suggest some redundancy of the pathway. The TNF receptor Troy acts redundantly with Edar in secondary hair follicle development (Pispa et al, 2008) and it would be interesting to investigate the role of Troy in SMG development. We also show that embryonic Eda Ta/Ta and Eda Ta/þ SMGs exhibit a similar branching defect.…”
Section: Discussion Eda Signaling Is Required For Normal Smg Branchinmentioning
confidence: 99%
“…These data, along with the present work, suggest some redundancy of the pathway. The TNF receptor Troy acts redundantly with Edar in secondary hair follicle development (Pispa et al, 2008) and it would be interesting to investigate the role of Troy in SMG development. We also show that embryonic Eda Ta/Ta and Eda Ta/þ SMGs exhibit a similar branching defect.…”
Section: Discussion Eda Signaling Is Required For Normal Smg Branchinmentioning
confidence: 99%
“…In developing teeth and hair follicles, the effects of Eda are mediated largely by transcription factor nuclear factor-kB (NF-kB) (Schmidt-Ullrich et al, 2001; Pispa et al, 2008). Inhibition of NF-kB in vitro by cell-permeable peptide SN50 was reported to inhibit SMG branching morphogenesis (Melnick et al, 2001a).…”
Section: Eda Signaling In Smg Is Mediated By Nf-kbmentioning
confidence: 99%
“…However, more recent studies by the same group (Melnick et al, 2009) suggested that NF-kB activity is not essential for Eda signaling in the salivary gland. To study this obvious discrepancy, we first analyzed NF-kB activity with a NF-kB lacZ reporter mouse (Bhakar et al, 2002;Pispa et al, 2008) in the developing salivary gland. At all stages studied (E12-E17), we observed strong NF-kB signaling activity in the epithelium ( Fig.…”
Section: Eda Signaling In Smg Is Mediated By Nf-kbmentioning
confidence: 99%
See 1 more Smart Citation
“…The EDA1-EDAR axis plays a predominant role in the development of skin-derived structures, whereas EDA2 and XEDAR, also known as EDA2R, have little or no role in this respect (20 -24). XEDAR is closely related to the orphan receptor TROY, and an NF-B-independent role for TROY in hair formation was identified in mice deficient for both TROY and EDA (25). TROY may bind to lymphotoxin ␣ (26), but our laboratory did not detect this interaction (27).…”
mentioning
confidence: 96%